AI Chatbots: Fast Tracking Sustainability Report Analysis for Enhanced Decision Making - Marcel Ioan Boloș; Ștefan Rusu; Claudia Diana Sabău-Popa; Dana Simona Gherai; Adrian Negrea a; Mihai-Ioan Crișan (Amfiteatru Economic, 2024)
This paper explores the integration of artificial intelligence (AI) in businesses, focusing on the utility of chatbots for sustainability report analysis. Using ChatGPT technology via the Chat-based platform, we developed a personalised chatbot to extract data from sustainability reports, with the aim of facilitating decision-making processes. The study includes a literature review on AI's impact on the economy and labour markets, followed by a methodology base on technology ChatGPT detailing chatbot development and testing using a sustainability report of a company listed on the Romanian stock market. The results demonstrate the efficacy in providing accurate financial insights, offering potential benefits for analysts, investors, and business organisations managers. By harnessing AI-powered chatbots, organisations can streamline operations and gain a competitive edge in today's digital landscape.